Cistanche deserticola polysaccharide induces melanogenesis in melanocytes and reduces oxidative stress via activating NRF2/HO‐1 pathway. Issue 7 (25th February 2020) - Hu, Yibo; Huang, Jinhua; Li, Yixiao; Jiang, Ling; Ouyang, Yujie; Li, Yumeng; Yang, Lun; Zhao, Xiaojiao; Huang, Lihua; Xiang, Hong; Chen, Jing; Zeng, Qinghai
Abstract: As a main part of pigmentation disorders, skin depigmentation diseases such as vitiligo and achromic naevus are very common and get more attention now. The pathogenesis of depigmentation includes melanocyte dysfunction and loss, which are possibly caused by heredity, autoimmunity and oxidative stress. Among them, oxidative stress plays a key role; however, few clinical treatments can deal with oxidative stress. As reported, Cistanche deserticola polysaccharide (CDP) is an effective antioxidant; based on that, we evaluated its role in melanocyte and further revealed the mechanisms. In this study, we found that CDP could promote melanogenesis in human epidermal melanocytes (HEMs) and mouse melanoma B16F10 cells, it also induced pigmentation in zebrafish. Furthermore, CDP could activate mitogen‐activated protein kinase (MAPK) signal pathway, then up‐regulated the expression of microphthalmia‐associated transcription factor (MITF) and downstream genes TYR, TRP1, TRP2 and RAB27A . Otherwise, we found that CDP could attenuate H2 O2 ‐induced cytotoxicity and apoptosis in melanocytes. Further evidence revealed that CDP could enhance NRF2/HO‐1 antioxidant pathway and scavenge intracellular ROS. In summary, CDP can promote melanogenesis and prevent melanocytes from oxidative stress injury, suggesting that CDP helps maintain the normal status of melanocytes. Thus, CDP may be a novel drug for the treatment of depigmentation diseases. Abstract : Cistanche deserticola polysaccharide (CDP) promotes melanogenesis in human epidermal melanocytes via activating mitogen‐activated protein kinase (MAPK) signal pathway, then up‐regulates the expression of MITF, TYR, TRP1, TRP2, and RAB27A . Otherwise, CDP can attenuate H2 O2 ‐induced oxidative stress in melanocytes via enhancing NRF2/HO‐1 antioxidant pathway and scavenge intracellular ROS.